2014
DOI: 10.1371/journal.pone.0105875
|View full text |Cite
|
Sign up to set email alerts
|

Viral RNAs Are Unusually Compact

Abstract: A majority of viruses are composed of long single-stranded genomic RNA molecules encapsulated by protein shells with diameters of just a few tens of nanometers. We examine the extent to which these viral RNAs have evolved to be physically compact molecules to facilitate encapsulation. Measurements of equal-length viral, non-viral, coding and non-coding RNAs show viral RNAs to have among the smallest sizes in solution, i.e., the highest gel-electrophoretic mobilities and the smallest hydrodynamic radii. Using g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
63
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 72 publications
(91 reference statements)
1
63
0
Order By: Relevance
“…In general, viral RNA is substantially more compact than nonviral sequences; Gopal and co-workers observed that large RNAs formed ellipsoidal structures. The hydrodynamic radius, R h , of a nonviral RNA was about half the radius of gyration one would calculate based on its length, and the R h for nonviral RNA was as much as twice that of viral RNA 39, 40 . Our data support the concept that compactness matters.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In general, viral RNA is substantially more compact than nonviral sequences; Gopal and co-workers observed that large RNAs formed ellipsoidal structures. The hydrodynamic radius, R h , of a nonviral RNA was about half the radius of gyration one would calculate based on its length, and the R h for nonviral RNA was as much as twice that of viral RNA 39, 40 . Our data support the concept that compactness matters.…”
Section: Discussionmentioning
confidence: 96%
“…PSS has a persistence length similar to that of a hypothetical ssRNA that lacks base-pairs but PSS has a smaller excluded volume due to the hydrophobic styrene side chains 38 . Conversely viral RNA, in general, has a pronounced tendency to form compact structures based on its density of base-pairing 39, 40 , thus our source of RNA is the P1 region of Bovine Enterovirus 41 . We found the particle yield and uniformity were sensitive to both substrate length and structure.…”
mentioning
confidence: 99%
“…Others, such as HOTAIR and NRON, are important regulators of gene expression (9)(10)(11) linked to diverse human diseases (12). Furthermore, a vast number of important pathogenic viruses including HIV, SARS coronavirus, poliovirus, Dengue fever virus, and many others utilize long RNAs as genetic material, which also play structural roles during virus assembly and genome packaging (13)(14)(15)(16)(17)(18)(19)(20). Previous studies have established the importance of local secondary and three-dimensional structure in the biological function of RNA (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have established the importance of local secondary and three-dimensional structure in the biological function of RNA (21,22). However, the effects of the secondary structure on the large-scale properties (e.g., size) of long RNAs remain poorly understood, even while its importance for virus assembly has been demonstrated (13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…STMV RNA is exceptionally extended, in contrast to the compactness predicted (Yoffe et al 2008) and observed (Gopal et al 2012(Gopal et al , 2014 for the RNA genomes of other spherical viruses. Compactness facilitates packaging into the small volume of the capsid for some viruses (Yoffe et al 2008;Cadena-Nava et al 2012;Gopal et al 2012;Garmann et al 2014a,b), and compactness has also been suggested as a basis for protection against RNA interference and other innate intracellular responses.…”
Section: Discussionmentioning
confidence: 65%